Unquenched Thirst: The Need For A Constitutionally Recognized Right To Water In Ghana - Crosby, Tia (Journal of Sustainable Development Law and Policy, 2025)
The practice of privatizing water is often discussed as the leading method for improving access to adequate water in developing countries. Notably, this method has a cost that frequently impedes access to water in the developing world, while exploiting the profitability of a natural resource that is vital to human life. In Ghana, the failure of water privatization initiatives and the growing scarcity of adequate water have caused a public health crisis that necessitates a quick and efficient solution. As demonstrated in South Africa, the codification of the right to water in its constitution has improved access to adequate water, sparked government concern and action on water and sanitation issues, and provided citizens with various avenues to compel government adherence to the constitutional right. Is constitutional recognition of the right to water an adequate alternative to privatization of water? If so, can such recognition solve Ghana’s water woes? This paper examines how constitutional recognition of the right to water in Ghana can successfully encourage the substantive realization of access to adequate water to all Ghanaians and an efficient procedural process that assures government accountability in water governance.